1995
DOI: 10.1021/jm00012a017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Protonation of Isophosphoramide Mustard and Phosphoramide Mustard

Abstract: The alkylating agent isophosphoramide mustard (IPM) spontaneously forms a relatively stable aziridine derivative which can be directly observed using NMR spectroscopy. The protonations of IMP and its aziridine were probed using 1H, 31P, 15N, and 17O NMR spectroscopy. The positions of the 31P, 15N, and 17O resonances of IPM between pH 2 and 10 each exhibit a single monobasic titration curve with the same pKa of 4.31 +/- 0.02. On the basis of a comparison with other compounds and our earlier work with phosphoram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 10 publications
(14 reference statements)
4
18
0
Order By: Relevance
“…The overall 31 P NMR chemical shift change of about 1.25 ppm suggests that protonation of 12b occurs on oxygen rather than nitrogen. 26,27 Synthesis of the analogous phosphorodiamidate peptidomimetic prodrugs 16 -18 is outlined in Schemes 5 and 6. Allyl ester 13a was prepared by reaction of p-aminobenzoic acid potassium salt with allyl bromide in DMF.…”
Section: C) Phosphorodiamidatesmentioning
confidence: 99%
“…The overall 31 P NMR chemical shift change of about 1.25 ppm suggests that protonation of 12b occurs on oxygen rather than nitrogen. 26,27 Synthesis of the analogous phosphorodiamidate peptidomimetic prodrugs 16 -18 is outlined in Schemes 5 and 6. Allyl ester 13a was prepared by reaction of p-aminobenzoic acid potassium salt with allyl bromide in DMF.…”
Section: C) Phosphorodiamidatesmentioning
confidence: 99%
“…In contrast, phosphorus amides are more susceptible to X-N cleavage at lower pH values than are carbonyl amides, and at least three possible mechanisms can account for the cleavage [11].…”
Section: Introductionmentioning
confidence: 97%
“…1. Biochemical studies suggest that IPM does not alkylate as a typical nitrogen mustard but rather as a phosphorodiamidate anion and may cross-link DNA differently from that of classical nitrogen and phosphoramide mustards [5,9,11]. As expected, the toxicities of IPM are different from those of ifosfamide and CPA [2][3][4]12].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[1][2][3] In published 1 and unpublished work, we have shown that phosphoramide mustard (PM, 1) and isophosphoramide mustard (IPM, 2) form aziridinyl intermediates which partition between two pathways: alkylation and P-N bond hydrolysis (Schemes 1 and 2). In the absence of a strong nucleophile, P-N bond scission accounts for up to 90% of the observed products.…”
Section: Introductionmentioning
confidence: 99%